2019
DOI: 10.2147/idr.s202906
|View full text |Cite
|
Sign up to set email alerts
|

<p>Molecular typing revealed the emergence of <em>pvl</em>-positive sequence type 22 methicillin-susceptible <em>Staphylococcus aureus</em> in Urumqi, Northwestern China</p>

Abstract: Background Staphylococcus aureus is among the most common causes of health care- and community-associated infections worldwide. The distributions of different S. aureus clones change over time and also vary geographically. The purpose of this study was to determine the molecular type and antimicrobial resistance profiles of clinical S. aureus strains isolated in Urumqi, Northwestern China. Methods A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 48 publications
(62 reference statements)
6
27
1
Order By: Relevance
“…Fu et al represented. Our finding differ from the recent studies that the most common SCCmec types were III in Guangdong and Xinjiang 27,28 and IV in Shanghai 29 and Trento. 30 In this study, AST also revealed that all or most of the isolates were susceptible to VAN, LZD, QUD, TST and NIT but were resistant to PEN, consistent with the results of most previous studies conducted in China and worldwide.…”
Section: Dovepresscontrasting
confidence: 99%
See 1 more Smart Citation
“…Fu et al represented. Our finding differ from the recent studies that the most common SCCmec types were III in Guangdong and Xinjiang 27,28 and IV in Shanghai 29 and Trento. 30 In this study, AST also revealed that all or most of the isolates were susceptible to VAN, LZD, QUD, TST and NIT but were resistant to PEN, consistent with the results of most previous studies conducted in China and worldwide.…”
Section: Dovepresscontrasting
confidence: 99%
“…The most prevalent sequence types in both the total S. aureus and MRSA isolates were ST5 and ST239, and this finding differs from other reports. 27 Specifically, the predominant MRSA isolates were ST5 and ST398 in Shanghai in 2017, 18 ST239 and ST338 in Guangdong during 2010-2016, 28 ST239 and ST15 in Iran during 2015-16 35 and ST5 and ST8 in the United States during 2010-2011. 36 The predominant MSSA genotypes were ST188 and ST7, which was in accordance with the majority of previous studies.…”
Section: Dovepressmentioning
confidence: 97%
“…36,37 In Iran, the rate of fusidic acid resistance, during a 4-year period on 726 tested S aureus isolates, was found to be 3%. 38 According to the evidence low level of resistance to fusidic acid is China (34.4%), 6 Ireland (17%), 36 and Lebanon (12%) 4 A high prevalence of SEs genes was observed in the present study (52%). it was similar to 62.6% prevalence SEs genes in a study of Turkey.…”
Section: Discussionsupporting
confidence: 47%
“…A high prevalence of pvl among ST22 MSSA strains has been reported by Yuan et al6 (80.8%). Different virulence determinants in CC/ST22 have been reported by researchers 6,36. Contrary to earlier data that indicated HLMUPR in ST22 strains,28,36 our analysis confirmed a 23.8% prevalence of LLMUPR in Iran.…”
mentioning
confidence: 73%
See 1 more Smart Citation